Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1037/a0037305
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing “continuity”: A qualitative investigation of waking life in dreams.

Abstract: Continuity between waking life and dreaming has typically been studied via the quantitative analysis of dream reports, which has illustrated that dreaming reflects waking-life experiences, thoughts, and emotions. However there are currently no reliable methods of analysing dreams for more subjective aspects of dreams, such as dreams that are metaphorically related to the dreamer's waking life. We conducted a qualitative study involving in-depth semi-structured interviews with four participants. The interview s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…To take an example from research, in an interview study we discussed with participants many aspects of dreams that were metaphors for their waking life, such as one participant’s dream of the ‘Starship Enterprise’ taking off from Earth representing her new entrepreneurial career ‘taking off,’ and another participant who dreamt of a demon being released as representing the release of his own ‘inner demon’ ( Malinowski et al, 2014 ). These dreams conformed to the three agreed elements of dream metaphors above: they concretely pictured something abstract from waking life; they were about emotional aspects of their life; and it was necessary to talk in detail with the dreamer about what was going on currently in their life in order to understand the metaphor.…”
Section: The Emotion Assimilation Theory Of Sleep and Dreamingmentioning
confidence: 99%
See 1 more Smart Citation
“…To take an example from research, in an interview study we discussed with participants many aspects of dreams that were metaphors for their waking life, such as one participant’s dream of the ‘Starship Enterprise’ taking off from Earth representing her new entrepreneurial career ‘taking off,’ and another participant who dreamt of a demon being released as representing the release of his own ‘inner demon’ ( Malinowski et al, 2014 ). These dreams conformed to the three agreed elements of dream metaphors above: they concretely pictured something abstract from waking life; they were about emotional aspects of their life; and it was necessary to talk in detail with the dreamer about what was going on currently in their life in order to understand the metaphor.…”
Section: The Emotion Assimilation Theory Of Sleep and Dreamingmentioning
confidence: 99%
“…The fact that dreams involve elements unknown to the dreamer (such as characters or activities that the dreamer has not had direct experience of in waking life) is not evidence against the notion of these being distant memory associations, because memory consolidation does not involve merely strengthening memories for literal recall, but also extraction of the gist of the memory ( Wamsley, 2014 ). Indeed, we have found that ‘generic’ elements occur frequently in dreams, such that people dream of recognizable ‘types’ – which come from an amalgamation of a variety of specific waking-life memories, but not any one particular memory – which are akin to ‘extras’ in a film ( Malinowski et al, 2014 ). For example, one participant dreamt of a generic bookshop and a generic bookshop assistant, which comes from a combination of various experiences of bookshops and bookshop assistants, but without being any particular place or person from memory.…”
Section: The Emotion Assimilation Theory Of Sleep and Dreamingmentioning
confidence: 99%
“…The procedure, detailed below, allows for the full describing of as much as can be remembered of the dream, the description by the dreamer of their recent waking life events and concerns before the dream, and the bringing together of these accounts of the dream and of waking life, so as to explore their connections. The Schredl dream group method (Schredl, 2007, 2011; Malinowski et al, 2014), also detailed below, aims to assist the dreamer in identifying common action and emotion patterns present in his or her dream and in his or her waking life. In both the Ullman and Schredl techniques, there is a phase in which the dream group can ask questions of the dreamer, in an attempt to consider connections between the content of the dream and the waking life experiences of the dreamer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have examined different kinds of continuity between dream and wake experiences include those by Schredl and Hofmann (2003), Hobson and Schredl (2011), Schredl (2000, 2003, 2006), Horton (2017), Horton and Malinowski (2011), Malinowski et al (2014), Malinowski and Horton (2011, 2015), Kahn and Hobson (2003, 2005a), Kahan and LaBerge (2011), Kahan et al (1997), Domhoff (2011), Kozmová and Wolman (2006), Samson and De Koninck (1986), Sutton et al (1994), Llewellyn (2011, 2013).…”
Section: Introduction: Continuity and Non-continuitymentioning
confidence: 99%